Pengaruh Susu Kedelai Terhadap Penurunan Gejala Hot Flush pada Wanita Klimakterium - Nova, Evy Roberta; Veronica, Septika Yani; Sanjaya, Riona; Sagita, Yona Desni (Journal of Current Health Sciences, 2021)
Menopause is a hypoestrogenic condition due to decreased function of the ovaries. This situation can cause changes in the system in the body of women who experience menopause. This causes complaints such as hot flushes. The incidence of women over 50 years of age entering menopause in Indonesia in 2020 is estimated to reach 30.3 million. Handling menopause by giving soy milk. The purpose of this study was to determine the effect of soy milk on the reduction of hot flush symptoms in pre-menopausal women at Cempaka Public Health Center, Sungkai Jaya District, North Lampung Regency in 2021. The type of research used is pre-experimental with a one-group pre-test and post-test design approach. The population in this study were premenopausal women aged 45-55 years who experienced hot flushes at the Cempaka Public Health Center. The sampling technique used was purposive sampling. The sample in this study amounted to 24 people who were given the intervention of giving 250 ml of soy milk 2 times a day for 14 days. Univariate and Bivariate analysis using dependent t-test. The results of the study the average symptom of Hot Flush before drinking soy milk was 7.17 (mild category). The average symptom of a Hot Flush after drinking soy milk was 4.92. There is an effect of soy milk on the reduction of hot flush symptoms in pre-menopausal women p-value of 0.000 (p less than 0.05). Based on the results of the study, it is suggested that health workers can provide information about the benefits of non-pharmacological treatments such as soy milk to reduce the symptoms of hot flushes in postmenopausal women.  Abstrak: Menopause merupakan suatu kondisi hipoestrogenik akibat penurunan fungsi dari ovarium. Keadaan ini dapat menyebabkan perubahan sistem pada tubuh wanita yang mengalami menopause. Sehingga menimbulkan keluhan-keluhan seperti hot flush. Angka kejadian wanita usia diatas 50 tahun yang memasuki menopause di Indonesia tahun 2020 diperkirakan mencapai 30,3 juta. Salah satu untuk penanganan menopause dengan memberikan susu kedelai. Tujuan penelitian adalah untuk mengetahui Pengaruh Susu Kedelai Terhadap Penurunan Gejala Hot Flush Pada Wanita Pra Menopause di Puskesmas Cempaka Kecamatan Sungkai Jaya Kabupaten Lampung Utara Tahun 2021. Jenis penelitian yang digunakan adalah pre eksperimental  dengan pendekatan one group pre test and post test desaign. populasi dalam penelitian ini adalah ibu premenopause berusia 45-55 tahun yang mengalami hot flush di Puskresmas Cempaka,  Tehnik sampling yang di gunakan yaitu purposive sampling Sampel dalam penelitian berjumlah 24 orang yang diberi intervensi pemberian susu kedelai 250 ml sebanyak 2 kali sehari selama 14 hari.. Analisa Univariat dan Bivariat menggunkan uji t dependen. Hasil penelitian Rata-rata gejala Hot Flush sebelum minum susu kedelai sebesar 7,17 (kategori ringan). Rata-rata gejala Hot Flush sesudah minum susu kedelai sebesar 4,92. Ada Pengaruh Susu Kedelai Terhadap Penurunan Gejala Hot Flush Pada Wanita Pra Menopause p value 0,000 (p kurang dari 0,05). Berdasarkan hasil penelitian disarankan petugas kesehatan dapat memberikan informasi tentang manfaat pengobatan non farmakologi seperti susu kedelai untuk mengurangi gejala Hot Flush pada ibu menopause.